"J.B." : a play in verse - MacLeish, Archibald, 1892-1982 (Houghton Mifflin, 1957)
A verse play. Dramatization of the theme of the Book of Job. A prosperous businessman loses his wealth, health and family, but maintains his faith in God. 2 acts, 11 men, 6 women, 1 boy, 3 girls, 1 interior.